Comparisson of methods for the analysis of total and fecal coliforms in water samples using the Most Probable Number technique - Redondo-Solano, Mauricio (2011)
The basic microbiological analysis of water includes the determination of total and fecal coliforms. The presence or abscense of fecal coliforms in water defines its potability. The main objective of this work was to design and execute a comparison scheme of two techniques for the determination of coliforms in water, applying modifications to the reference technique of the Most Probable Number, derived from the Standard Methods for the Examination of Water and Wastewater. The modifications included the type of media used for the presumptive phase and the use of an air incubator instead of a water bath for the confirmatory phase. At the same time, the effect of using calibrated automatic pipettes and calibrated glass pipettes was also compared. Artificial water samples, elaborated with standard laboratory material and inoculated with Escherichia coli ATCC 25922 and environmental samples, were used. The alternative methodology shows a superior performance only when inoculation is low. There was no difference between the two volumetric systems.